2018
DOI: 10.1200/jco.2017.74.8392
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel With Inhibitor of Apoptosis Antagonist, LCL161, for Localized Triple-Negative Breast Cancer, Prospectively Stratified by Gene Signature in a Biomarker-Driven Neoadjuvant Trial

Abstract: Purpose There are currently no targeted therapies approved for triple-negative breast cancer (TNBC). A tumor necrosis factor α ( TNFα)–based gene expression signature (GS) predictive of sensitivity to LCL161, inhibitor of apoptosis antagonist, was translated into a clinical assay and evaluated in a neoadjuvant trial. Patients and Methods Women with localized TNBC (T2/N0–2/M0) were prospectively stratified by GS status and randomly assigned (1:1) to receive oral LCL161 (1,800 mg once per week) and intravenous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…The reported preclinical studies and clinical trials reported the observation that high anticancer efficacy of PTX/LCL161 co-therapies (including breast and lung cancers) [47][48][49]. Our discovery of the essential role of memTNF-mediated cell death in these effects defines the mechanistic rationale that can explain how this observed synergism actually occurs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The reported preclinical studies and clinical trials reported the observation that high anticancer efficacy of PTX/LCL161 co-therapies (including breast and lung cancers) [47][48][49]. Our discovery of the essential role of memTNF-mediated cell death in these effects defines the mechanistic rationale that can explain how this observed synergism actually occurs.…”
Section: Discussionmentioning
confidence: 90%
“…Given that IAP proteins block apoptosis caused by TNF, and considering that IAP antagonists have profound effects in potentiating solTNF-induced apoptosis [44][45][46], we hypothesized a combination treatment with IAP antagonists Smac mimetics (S) would further sensitize cancer cells to MTA-induced apoptosis. Currently, several Smac mimetics are being evaluated in clinical trials (https://clinicaltrials.gov) and combination of LCL161 with PTX has shown synergistic effects on several cancers [47][48][49], but the mechanism remains largely unknown.…”
Section: Mta-induced Memtnf-mediated Apoptosis Can Be Potentiated By mentioning
confidence: 99%
“…As discussed above, the chemotherapy paclitaxel has been shown to potentiate LCL161 mediated killing in solid tumors, including Triple Negative Breast Cancer (TNBC) [124,[134][135][136]. Phase II clinical trials were initiated [137], following Phase I trials that indicated that LCL161 plus paclitaxel therapy is well tolerated [134]. Interestingly, for this study the TNF-based Gene expression Signature (GS) was determined for each patient and used as a predictor of sensitivity to SM-mediated cell death [137].…”
Section: Combination With Chemotherapymentioning
confidence: 99%
“…Phase II clinical trials were initiated [137], following Phase I trials that indicated that LCL161 plus paclitaxel therapy is well tolerated [134]. Interestingly, for this study the TNF-based Gene expression Signature (GS) was determined for each patient and used as a predictor of sensitivity to SM-mediated cell death [137]. Bardia and colleagues conducted a global trial incorporating molecular pre-screening to investigate the neoadjuvant treatment of LCL161 and paclitaxel in TNBC patients assigned as GS-positive (more likely to respond to SM treatment) vs. GS-negative (less likely to respond) [137].…”
Section: Combination With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation